Imaging of Acquired Demyelinating Syndrome With 18F-FDG PET/CT. (February 2018) - Malo-Pion, Caroline; Lambert, Raymond; Décarie, Jean-Claude; Turpin, Sophie
Abstract : Abstract: Acquired demyelinating syndromes include acute disseminated encephalomyelitis, transverse myelitis and may progress to multiple sclerosis (MS). Acute disseminated encephalomyelitis is characterized by impairment of level of consciousness and multifocal neurological deficits and transverse myelitis by back pain, weakness and sphincter dysfunction. Only a few cases of acquired demyelinating syndrome have been imaged with 18 F-FDG PET/CT. We present two such cases.